First Oral Vaccination of Eurasian Wild Boar Against African Swine Fever Virus Genotype II - Barasona, Jose A.; Gallardo, Carmina; Cadenas-Fernández, Estefanía; Jurado, Cristina; Rivera, Belén; Rodríguez-Bertos, Antonio; Arias, Marisa; Sánchez-Vizcaíno, Jose M. (Frontiers in Veterinary Science, 2019)
African swine fever (ASF), the most significant threat to the pig industry worldwide, has spread to more than 55 countries on three continents, and it affects more than 77% of the world swine population. In the European Union, wild boar (Sus scrofa) is the most severely affected host. The main reasons for the unprecedented and constant spread of ASF in Europe are the trade activities, the continuous movement of infected-wild boar populations among regions and the lack of vaccine to prevent ASF infection. In this study, we demonstrate that oral immunization of wild boar with a non-hemadsorbing, attenuated ASF virus of genotype II isolated in Latvia in 2017 (Lv17/WB/Rie1) conferred 92% protection against challenge with a virulent ASF virus isolate (Arm07). This is, to our knowledge, the first report of a promising vaccine against ASF virus in wild boar by oral administration. Further studies should assess the safety of repeated administration and overdose, characterize long-term shedding and verify the genetic stability of the vaccine virus to confirm if Lv17/WB/Rie1 could be used for free-ranging wild boar in ASF control programs.